Cover Picture: Recent Development of Aprotic Na−O2 Batteries (Batteries & Supercaps 9/2019). Issue 9 (29th August 2019) - Zhao, Shuo; Qin, Bin; Chan, Kwong‐Yu; Li, Chi‐Ying Vanessa; Li, Fujun
Abstract : The Front Cover illustrates an aprotic Na‐O2 battery using Na as the metal anode and a porous oxygen diffusion cathode with NaO2 as the discharge product. The authors summarized the most recent publications in this topic. More information can be found in theReview by S. Zhao et al .